Faith-Based Consumer Behavior: The Role of Religiosity in Shaping Customer Loyalty in Islamic Banking - Wulandjani, Harimurti (Jurnal Ragam Pengabdian, 2025)
This study examines the effect of religiosity on customer loyalty among Bank Syariah Indonesia (BSI) customers from a faith-based consumer behavior perspective. A quantitative approach with a causal cross-sectional design was employed. Data were collected through questionnaires from 301 BSI customers selected using purposive sampling. Religiosity was measured using indicators adapted from Usman (2016), while customer loyalty was measured using the scale developed by Harris and Goode (2004). Data were analyzed using IBM SPSS Statistics 27 through validity and reliability tests, classical assumption tests, simple linear regression, hypothesis testing, and coefficient of determination analysis. The findings indicate that religiosity has a positive and significant effect on customer loyalty. Customers with stronger religious commitment tend to demonstrate greater loyalty toward Islamic banking services. These findings support the faith-based consumer behavior perspective, suggesting that religious values remain an important factor influencing consumer attitudes and loyalty in Islamic banking.